Effects of Sevelamer Hydrochloride and Calcium Carbonate on Renal Osteodystrophy in Hemodialysis Patients - Ferreira, A (2008)
Disturbances in mineral metabolism play a central role in the development of renal bone disease. In a 54-wk, randomized, open-label study, 119 hemodialysis patients were enrolled to compare the effects of sevelamer hydrochloride and calcium carbonate on bone. Biopsy-proven adynamic bone disease was the most frequent bone abnormality at baseline (59%). Serum phosphorus, calcium, and intact parathyroid hormone were well controlled in both groups, although calcium was consistently lower and intact parathyroid hormone higher among patients who were randomly assigned to sevelamer. Compared with baseline values, there were no changes in mineralization lag time or measures of bone turnover (e.g., activation frequency) after 1 yr in either group. Osteoid thickness significantly increased in both groups, but there was no significant difference between them. Bone formation rate per bone surface, however, significantly increased from baseline only in the sevelamer group (P = 0.019). In addition, of those with abnormal microarchitecture at baseline (i.e., trabecular separation), seven of 10 in the sevelamer group normalized after 1 yr compared with zero of three in the calcium group. In summary, sevelamer resulted in no statistically significant changes in bone turnover or mineralization compared with calcium carbonate, but bone formation increased and trabecular architecture improved with sevelamer. Further studies are required to assess whether these changes affect clinical outcomes, such as rates of fracture.